APPLIED ORIENTATION OF TEACHING STOCHASTIC METHODS TO ENGINEERING STUDENTS - Abylkasymova, A.E.; Тuyakov Е.А.; Rysbekova , G.A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The application of stochastic techniques as a tool for enhancing the quality of the technical specialties’ educational process is investigated in this paper. Particularly relevant in the framework of fast technical and digitalization advancements, these approaches enable the modeling of complicated industrial processes and solving of problems under conditions of uncertainty. The research emphasizes the development of strategies for instructing stochastic procedures inside educational curricula designed to cultivate technical specialists. The primary objective of this study is to enhance students’ analytical thinking, forecasting, and decision-making skills in unconventional situations, thereby allowing educational processes to align with the requirements of contemporary industrial sectors. The scientific and pragmatic relevance of the research is found in the fact that stochastic approaches enable the combination of theoretical knowledge with practical skills, therefore facilitating the training of highly qualified experts ready to operate in dynamic and complex systems. The study approach called for theoretical modeling, data analysis, and investigation of real-world examples. By means of production scenario modeling, the outcomes were acquired, therefore highlighting the efficiency of stochastic methods in addressing practical issues. The results of the research suggest that using stochastic approaches helps students to acquire their data analysis, process management under uncertainty, and modern digital tool application abilities. The approach significantly helps to create adaptable learning environments meant to solve industrial challenges. The practical relevance of the research findings is in their usefulness for the creation of educational programs meant to equip graduates fulfilling the criteria of digital transformation and modern industries.